Turbocharging Deep Backscatter Through Constructive Power Surges with a Single RF Source - An, Zhenlin; Lin, Qiongzheng; Pan, Qingrui; Yang, Lei (Annual Joint Conference of the IEEE Computer and Communications Societies, 2021)
Backscatter networks are becoming a promising solution for embedded sensing. In these networks, backscatter sensors are deeply implanted inside objects or living beings and form a deep backscatter network (DBN). The fundamental challenges in DBNs are the significant attenuation of the wireless signal caused by environmental materials (e.g., water and bodily tissues) and the miniature antennas of the implantable backscatter sensors, which prevent existing backscatter networks from powering sensors beyond superficial depths. This study presents RiCharge, a turbocharging solution that enables powering up and communicating with DBNs through a single augmented RF source, which allows existing backscatter sensors to serve DBNs at zero startup cost. The key contribution of RiCharge is the turbocharging algorithm that utilizes RF surges to induce constructive power surges at deep backscatter sensors in accordance with the FCC regulations, for overcoming the turn-on voltage barrier. RiCharge is implemented in commodity devices, and the evaluation result reveals that RiCharge can use only a single RF source to power up backscatter sensors at 60 m distance in the air (i.e., 10x longer than a commercial off-the-shelf reader) and 50 cm-depth under water (i.e., 2x deeper than the previous record).